Assessment of Anthropogenic Volatile Organic Compounds in Leaves of Two Urban Tree Species in Santiago de Chile - Araya, Mauricio; Seelenfreund, Daniela; Buscaglia, Marianne; Peña-Ahumada, Barbara; Vera, Javier; Egas, Claudia; Préndez, Margarita (Frontiers in Forests and Global Change, 2019)
Anthropogenic volatile organic compounds (AVOCs) represent the third largest contribution in gaseous emissions in the urban and peri-urban region of Santiago, the capital of Chile. Some of these compounds are toxic or mutagenic, cause serious damage to human health, and decrease plant growth and development. There is little international information related to atmospheric AVOCs in leaf content from trees exposed to specific sources of pollution, and to our knowledge, there is no research on this topic in Chile. The purpose of this work was to study the leaf content of AVOCs from the Organic Range of Gasoline (ORG: range 6–10 C) emitted by local traffic during the austral summer and spring seasons in leaves of two exotic tree species (Liriodendron tulipifera and Platanus × acerifolia). Leaf samples collected around 2 meters height above the ground were pulverized with a cryogenic mill and eleven chemical components were quantified (toluene, 1,2,4-trimethylbenzene (1,2,4-TMB), styrene, ethylbenzene, ortho, meta and para-xylenes, naphthalene, 1,3,5-trimethylbenzene (1,3,5-TMB), isopropylbenzene, and trichloroethene) using GC-MSD MSD. Benzene was detected but not quantified, because it was always under the quantification limit of the technique. Differences in concentrations were found for type of site exposure, season and tree species. The differences found in leaf content of AVOCs in P. × acerifolia exposed to vehicle traffic suggest that the concentration of these contaminants in leaves may be due to AVOC capturing. Considering the content of AVOCs in leaves and not in the whole individual tree, L. tulipifera presented a higher concentration of total AVOCs than P. × acerifolia for both seasons. The Prop-Equiv and OFP of L. tulipifera were very high in summer, being 13.6 and 14.8 times greater, respectively, than the corresponding values for P. × acerifolia.